Low albumin-to-creatinine ratio: a novel predictor of 90-day mortality in hepatocellular carcinoma with liver cirrhosis - Kadek Mercu Narapati Pamungkas; Putu Itta Sandi Lesmana Dewi; Ni Luh Putu Yunia Dewi; Ni Nyoman Gita Kharisma Dewi; Dwijo Anargha Sindhughosa; I Ketut Mariadi (Universa Medicina)
Background Despite recent advances in the treatments of hepatocellular carcinoma (HCC), the prognosis of HCC patients remains controversial. Lowered serum albumin in hepatocellular carcinoma, an advanced stage of liver cirrhosis, indicates a worsening condition. Hepatorenal syndrome, marked by increased serum creatinine, is a key mortality indicator. The aim of this study was to determine the serum albumin-to-creatinine ratio (sACR) as a predictor of mortality in patients with HCC and liver cirrhosis.